Time series analyses of Egyptian CPI rates during the Ukraine-Russa war: SARIMA and Holt-Winters models - Ibrahim, Maha Faruq Tawfiq (المجلة العلمية للدراسات و البحوث المالية و التجارية : علمية محكمة., 2023)
يواجه صانعو القرار دائما تحديا كبيرا في تحليل بيانات السلاسل الزمنية وهو محاولة العثور على أفضل نموذج للتنبؤ بالقيم المستقبلية نماذج السلاسل الزمنية للمتوسط المتحرك الموسمي المتكامل الانحدار الذاتي (SARIMA)، وطريقة هولت وينترز (Holt-Winters method) هي أساليب إحصائية تتنبأ بالقيم المستقبلية من خلال تحليل القيم السابقة. ويعد لكلاهما دورا مهما في العديد من المجالات العملية التي تعتمد على بيانات السلاسل الزمنية الموسمية. تأتي هذه الدراسة لبناء نموذج سلسلة زمنية مناسبة لمؤشر أسعار المستهلك المصري الشهري (CPI) خلال حرب أوكرانيا وروسيا والتنبؤ باستخدام بيانات (CPI) من يناير ۲۰۱۸ حتى يونيو ۲۰۲۲ باستخدام أدوات نموذج المتوسط المتحرك المتكامل للانحدار الذاتي الموسمي (SARIMA) وأداة طريقة Holt-Winters المتوفرة في 26-SPSS أوضحت نتائج الدراسة أن النماذج المقترحة أظهرت أنها كافية بالنسبة للمشاهدات الأصلية كما يظهر أن تنبؤاتها تتفق بشكل وثيق. أيضا، وفقا للمؤشرات الإحصائية، واكدت أن Winters additive أعطت تنبؤا أفضل من (0ـ1ـ0)) ARIMA (12 (0,0,1) لبيانات مؤشر أسعار المستهلكين المصري الشهرية. Decision makers always have big challenge in analyze time series data. it is how to find the best forecasting model. time series models seasonal autoregressive integrated moving average (SARIMA), and holt-winters method) are methods that predict future values by analyzing past values. it plays an important role in many practical fields that depending on seasonal time series data. this study is amid to build a good fit time series model of monthly Egyptian consumer price index (CPI) during the Ukraine-Russa war and forecasting the future values, using (CPI) data from Jan 2018 until June-2022. applied on autoregressive integrated moving average (SARIMA) model and holt-winters method tool available in SPSS-26. the result reveal that the proposed models is shown to be adequate and with the original observations its forecasting is shown to agree closely. also, according to the statical indicators, a winters additive is better forecasting than ARIMA ((0,1,0) (0,0,1)12) model) for the monthly Egyptian CPI data.